Pattern of breast lesions on fine-needle aspiration cytology in consecutive 70 cases: a retrospective and prospective analysis of one year - Singh, Roma; Saproo, Nipun (International Journal of Research in Medical Sciences, 2016)
Background: Breast lumps constitute a significant proportion of surgical cases in both developed and developing countries. In outpatient department breast lump is one of the commonest presentations, majority of them are in women and are benign. It is needed to distinguish benign lumps from malignant preoperatively for definite treatment. Methods: The present study is a retrospective and prospective study of one year and spans duration from 1st January 2015 to 31st December 2015, a total 70 cases were studied which included 67 female patients and 03 male patient. This study is been conducted in the department of pathology, L.N medical college and Associated J.K Hospital and research centre Bhopal (Madhya Pradesh). Cytomorphological features of breast lesions were studied and correlated with clinical and histological features. Results: The present study was conducted on 70 patients with palpable breast lump. Fibroadenoma was the most common benign breast lesion encountered and lump was the most common symptom. Conclusion: Most of the breast lesions are benign and needs only reassurance. The FNAC gives result very fast and is accurate therefore FNAC is useful in those cases, to avoid fear of surgery, benign breast lesions commonly affect the younger age group. Fibroadenoma is the most common lesion encountered in benign breast lesions.